THE LEADERSHIP OF THE MADRASAH HEAD IN FORMING THE QUALITY OF EDUCATORS AT MI AL-ITTIHAD JOGOROTO JOMBANG - Nur Zaidah (Media Inovasi Pendidikan dan Publikasi, 2023)
The success and quality of education in a madrasah can be said to be achieved when the school principal is of high quality and competent, as well as the teachers. Therefore, the school principal must have the ability to empower the teachers to conduct effective and high-quality teaching and learning processes, smoothly, proactively, and within designated timelines. Hence, the role and responsibilities of the School Principal's Leadership in shaping teacher quality are crucial, ensuring that all educators can carry out the teaching and learning process effectively. The objective of this research is to understand and analyze the leadership model of the madrasah principal and the quality of teachers at MI AL-ITTIHAD Jogoroto Jombang. This research adopts a qualitative approach, employing a case study methodology. The researcher's presence is integral as the key instrument and direct observer. Data for this study are sourced from the School Principal at MI AL-ITTIHAD Jogoroto Jombang, students, and the teacher council, selected through purposive sampling and collected using various data collection techniques, including observation, interviews, and documentation. The collected data are then analyzed using the Miles and Huberman analysis technique. The findings of this research indicate that the leadership model implemented by the madrasah principal at MI AL-ITTIHAD Jogoroto Jombang aligns with their role. In essence, the leadership model of the madrasah principal utilizes more than one model in shaping teacher quality, specifically the charismatic and transformative leadership styles. The establishment of teacher quality at MI AL-ITTIHAD is fairly commendable, demonstrated through the creation of educational tools such as Annual Programs, Semester Programs, Lesson Implementation Plans, effective delivery of subject matter, thereby fulfilling the teaching role. Additionally, a conducive and safe learning environment is established, alongside media tailored to the subject matter, equitable treatment of students, and systematic implementation of evaluations. Teachers possess a Strata 1 academic qualification, teaching certification, attend training and workshops to enhance competencies, exhibit exemplary morals, polite communication, and patience. Nonetheless, some teachers exhibit less refined communication during classroom instruction, while others exhibit impatience when dealing with non-academic student issues. Overall, the teacher quality at MI AL-ITTIHAD Jogoroto Jombang reflects their competency.